Comparative characteristics of patients with a combination of obstructive sleep apnea and paroxysmal atrial fibrillation in the groups of interventional and conservative treatment of arrhythmia - N. T. Obukhova; M. V. Agaltsov; O. M. Drapkina (Российский кардиологический журнал)
Aim. To compare the clinical characteristics of two groups of patients with a combination of obstructive sleep apnea (OSA) and paroxysmal atrial fibrillation (AF), undergoing conservative treatment for arrhythmia and after pulmonary vein isolation.Material and methods. The study included 362 patients with paroxysmal AF who underwent respiratory sleep monitoring.Results. A predominance of clinically significant OSA was revealed (moderate and severe — 37% and 29%, respectively), as well as a higher drug burden and comorbidity in the group of patients receiving drug treatment for AF. The threshold value of body mass index (BMI), at which a high risk of severe OSA was predicted, corresponded to class 1 obesity (BMI ≥31 kg/m2). The results obtained demonstrated an association between an increase in the left atrium anteroposterior size and the severity of OSA (4,1 [3,8-4,4] cm, r=0,28; p<0,001), which may be due to cardiac structural remodeling in patients with a combination of paroxysmal AF and severe OSA.Conclusion. In a cohort of patients with paroxysmal AF, a high incidence of clinically significant OSA was revealed. In the group of patients with a combination of OSA and AF undergoing conservative treatment, more unfavorable cardiovascular characteristics and a more severe comorbid status were revealed compared to the group of patients undergoing surgical treatment.